An aryl-fused redox-active tetrathiafulvalene with enhanced mixed-valence and radical-cation dimer stabilities. Issue 15 (29th March 2018) - Schröder, Hendrik V.; Witte, Felix; Gaedke, Marius; Sobottka, Sebastian; Suntrup, Lisa; Hupatz, Henrik; Valkonen, Arto; Paulus, Beate; Rissanen, Kari; Sarkar, Biprajit; Schalley, Christoph A.
Abstract : Enhanced mixed-valence and radical-cation dimer stabilities were found for an extended tetrathiafulvalene. Abstract : Molecular recognition of stable organic radicals is a relatively novel, but important structural binding motif in supramolecular chemistry. Here, we report on a redox-switchable veratrole-fused tetrathiafulvalene derivativeVTTF which is ideally suited for this purpose and for the incorporation into stimuli-responsive systems. As revealed by electrochemistry, UV/Vis measurements, X-ray analysis, and electrocrystallisation, VTTF can be reversibly oxidised to the corresponding radical-cation or dication which shows optoelectronic and structural propterties similar to tetrathiafulvalene and tetrakis(methylthio)tetrathiafulvalene. However, theoretical calculations, variable temperature EPR, and NIR spectroscopy indicate that the dispersion-driven binding in the mixed-valence dimer (VTTF 2 )˙ + ( K MV = 69 M −1 in CH2 Cl2 ) and the radical-cation dimer (VTTF ˙ + )2 ( K RC = 38 M −1 in CH3 CN) is significantly enhanced by the additional veratrole π-surface in comparison to pristine tetrathiafulvalene.